Detective and Family: : The Representation of Same-Sex Family in Holmes & Moriarity by Josh Lanyon - Wichiansri, Kanokwan; Chaochuti, Thosaeng (Journal of Letters, 2025)
This paper aims to study the questioning of in heteronormativity in early detective fiction by investigating the representation of homosexual family in the crime fiction series Holmes & Moriarity by Josh Lanyon. The study finds that the representations of the male detective and homosexual family are influenced by heteronormative standards. The selected texts raise questions about the conventions of early detective fiction that usually offer stereotypical representations of the male detective. The male detective in early detective fiction typically prefers a life of solitude and refuses to start a family. The selected texts, however, portray a protagonist who is able to perform his role as a detective while starting a family with his homosexual partner. The selected texts also try to represent a same-sex family that is different from a straight family. However, even same-sex partners are influenced by social norms and the concept of the ideal family. The representation of same-sex family in Holmes & Moriarity is, therefore, still unable to truly defy the dominant heteronormative standards.